Upaya Hukum Rehabilitasi terhadap Penyalahgunaan Narkotika menurut Undang-undang No 35 tahun 2009 tentang Narkotika - Praditya, Erry; Tejamukti, Robby; Yasarman, Yasarman (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2025)
Law No. 35 of 2009 on Narcotics introduces a significant paradigm shift in handling narcotics abuse in Indonesia. The previous paradigm under Law No. 22 of 1997, which focused mainly on repressive measures, has evolved into a more comprehensive approach that integrates repressive, rehabilitative, preventive, and restorative dimensions. Articles 54, 55, and 103 mandate that drug users and addicts undergo medical and/or social rehabilitation, emphasizing that they should not be regarded solely as criminals but also as victims in need of recovery. This study employs a normative juridical approach by analyzing legislation and related legal instruments, such as Supreme Court Circular No. 4 of 2010 jo. Circular No. 3 of 2011. The findings show that the legal paradigm in the Narcotics Law strikes a balance between legal certainty, human rights protection, and social recovery objectives. Thus, rehabilitation policies are expected to reduce the rate of narcotics abuse while protecting Indonesia’s young generation.